فکرِ اقبال کے چند اہم موضوعات سے متعلق پروفیسر عبد الحق کے افکارکا مطالعہProf. Abdul Haq on Important Themes of Iqbal’s Philosophy (Al-Qamar, 2021)
Prof. Abdul Haq is an honorable Iqbal scholar of India. He has precisely presented Iqbal's ideas according to Iqbal's thinking. Iqbal compared the Western concept of nationhood to the concept of the Nation of Islam. By Muslim nation, Iqbal always meant the nation of Islam. According to Iqbal, the basis of Muslim state is Islam. Iqbal opposes genocidal nationalism. There is no difference between Iqbal's theory of nationality and universality. Iqbal has also criticized the geographical concept of patriotism. His concept extended from the homeland to the universe. He was against the idea of worshipping state as idol. Iqbal's concept about 'man of faith' is also an admirable subject of thought and philosophy. According to him, the man of faith captures life and the universe. The fulfillment of ideality reaches its completion under the shadow of the self. Reading this article will make the understanding of Iqbal's concept much easy. The scope of the research will be widened. New themes will be created. New sources will be available.
Keywords: Iqbal's concept of nationalism and patriotism